U.S. INDO–PACIFIC STRATEGY: THE UTILIZATION OF THE U.S.– AUSTRALIA MILITARY ALLIANCE AS PART OF THE U.S. BALANCE OF POWER STRATEGY TO RESPOND TO CHINA INFLUENCE IN INDO–PACIFIC REGION - Reynaldo Rudy Kristian Montolalu (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
One of the U.S. intentions in Indo–Pacific is to counter a new rising giant of China. The U.S. government has recognized China as a competitive actor. An effort to promote U.S. security interests in the Indo–Pacific region serves as an option to safeguard their national interest. The U.S. alliance network is considered one of the most lasting and successful parts of U.S. Foreign Policy since World War II. The member of its alliance has adapted to several changes in international events, including in the post-Cold War era, the rivalry tended to be centered between two major powers. Australia is not the exception. Several bilateral and multilateral approaches to implementing its Mutual Defense Treaty have been integrated and enhanced. This study aims to elaborate on the U.S.–Australia Military Alliance as part of the U.S. Balance of Power Strategy to respond to China's Influence in Indo-Pacific Region. The study will use an explanatory research method by explaining rather than describing the studied phenomena that depart from the qualitative approach. In the end, the study concludes that the U.S. is actively involved with Australia as its military alliance through ANZUS, the Quad, and AUKUS; those all considered the effort encountered by the U.S. to respond to China's Influence in the Indo–Pacific Region